2019
DOI: 10.2147/ott.s200324
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anlotinib is effective in the treatment of advanced carcinoma ex pleomorphic adenoma of the submandibular gland</p>

Abstract: Background: Carcinoma ex pleomorphic adenoma (CXPA), a very rare malignancy found mostly in the major salivary glands, has no established standardized treatment. Case presentation: This report describes a 67-year-old male with advanced CXPA who was effectively treated by anlotinib. Pleomorphic adenoma of the submandibular gland was first diagnosed in 1976 after a surgical resection of a mass underneath the jaw. The patient underwent re-excision 3 years later due to a recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…TTF-1, CDX-2, CK7, and CK20 Immunohistochemistry helps identify cancer cells' tissue origin. Primary lung adenocarcinoma was positive for TTF-1, NapsinA, CK7, CK8, CK18 (24)(25)(26). Primary lung squamous cell carcinoma was positive for P40, P63, and CK5/6(26).…”
Section: Discussionmentioning
confidence: 99%
“…TTF-1, CDX-2, CK7, and CK20 Immunohistochemistry helps identify cancer cells' tissue origin. Primary lung adenocarcinoma was positive for TTF-1, NapsinA, CK7, CK8, CK18 (24)(25)(26). Primary lung squamous cell carcinoma was positive for P40, P63, and CK5/6(26).…”
Section: Discussionmentioning
confidence: 99%
“…The management of SMG‐CXPA includes an ablative surgical procedure, postoperative radiotherapy or chemotherapy (Iino et al, 2008; Song et al, 2019). Among these modalities, neck dissection is an important part of surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Soares et al [ 8 ] reported a gradual but significant increase in angiogenesis during the transformation from PA to the extensively aggressive Ca ex PA. Fonseca et al [ 10 ] found that VEGF expression was significantly high in malignant salivary gland tumors compared to benign tumors, suggesting that VEGF is involved in the pathogenesis and aggression of salivary gland tumors. These findings implied that inhibition of the VEGF signaling pathway is a potential treatment approach for Ca ex PA. Song et al [ 11 ] reported a patient with advanced Ca ex PA who achieved partial response after anlotinib monotherapy. However, in the current case, the patient suffered disease progression after 50 days of single-agent anlotinib treatment.…”
Section: Discussionmentioning
confidence: 99%